Habituation and Dishabituation in Motor Behavior: Experiment and Neural Dynamic Model - Aerdker, Sophie; Feng, Jing; Schöner, Gregor (Frontiers in Psychology, 2022)
Habituation and dishabituation are well-known phenomena of infant perception and cognition. In a sense, habituation reflects the destabilization of an orientation response. Dishabituation reflects the preferred orientation to a novel stimulus. Familiarity preference is often observed early in the process of habituation and may reflect the stabilization of the orientation response. In motor tasks, perseveration may be a signature of such a stabilization process. Does motor behavior also entail destabilization, leading to habituation and novelty preference? We report an experiment in which the typical habituation paradigm is applied to a motor task. The results provide evidence for habituation to a simple movement, dishabituation to a new movement, and Spencer-Thompson dishabituation to the initial movement. We account for the experimental data by a neural dynamic model that unifies previous accounts of perseveration, modeled by the build-up of activation in a neural dynamic field, and habituation, modeled by the build-up of inhibition in a neural dynamic field. We show that the unified model can be applied to selection tasks as well and reproduces the pattern of early familiarity and late novelty preference. Beyond development the neural dynamic account of stabilization and destabilization of object-directed actions may speak to the balance between exploitation and exploration of objects and actions.